ANALISA BREAK EVEN POINT (BEP) PADA RICE MILLING MACHINE “ BAROKAH “ DI TIRTO KABUPATEN PEKALONGAN - Edi Purnomo, Djauhar; Pujiono, Akhmad (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Indonesia is an agricultural country where the majority of the population consists of farmers so that the agricultural sector plays an important role. The agricultural sector is a source of life for the majority of the population, especially for those who have their main livelihood as farmers. In addition, the agricultural sector is one of the important things that must be considered as a provider of food for the community. Profit planning requires a tool in the form of profit volume cost analysis. Costs, volume and profits are the three main elements in preparing a profit and loss statement for a business. In carrying out its operational activities, a management company will try to obtain and allocate resources in a way that is the cheapest in terms of cost and provides the most benefits in achieving business goals. This study discusses the analysis of the break even point (Break Even Point) in the Rice Milling Machine